Characterizing the Brittle Fracture and the Ductile to Brittle to Ductile Transition of Heat-Treated Binary Aluminum-Lithium Alloys - Fragomeni, J.M. (Engineering Transactions, 2001)
An aluminum alloy containing 2.6wt.% Li and 0.09wt.% Zr exhibited a very low value in tensile ductility consistently prior to the peakaged strength independent of thermal treatment. A transition was characterized by very low ductility in the slightly underaged condition up to the near peakaged condition, then followed by a substantial increase in ductility with aging after the peakaged treatment. In order to better understand the deformation and fracture, a scanning electron microscopy study of the fracture surfaces of Al-2.6wt.% Li-0.09wt.% Zr tensile samples solution heat-treated and artificially aged was performed to relate the mechanical behavior to microstructure in the precipitation hardened Al-Li alloy. SEM analysis of the surface features and fracture morphology of the alloy was performed to understand the mechanisms of fracture in relation to the ductile-to-brittle transition that resulted in the alloy from precipitation hardening. TEM analysis was also performed to characterize the deformation behavior, and revealed the distribution of precipitates (both Al$_3$Li ($δ^′$) and Al$_3$Zr-Al$_3$Li) in the microstructure at very high magnifications as well as the dislocation subgrain structure of the alloy at lower magnification. It follows from this study that the presence of $δ^′$ particles in the matrix promotes intense planar slip which was believed to be responsible for the ultra-low ductility prior to the peakaged temper. Based on a detailed quantitative microscopy study, it was proposed that the increase in the ductility of the alloy after aging was a consequence of particle coarsening with aging thus resulting the Orowan process due to the transition from dislocation particle shearing to dislocation particle bypassing.